Influences of low-energy input microwave and ultrasonic pretreatments on single-stage and temperature-phased anaerobic digestion (TPAD) of municipal wastewater sludge - AKGÜL, DENİZ (PERGAMON-ELSEVIER SCIENCE LTD, 2017)
The effect of low energy-input (2.5 IcJig total solids) microwave (MW) irradiation and ultrasonication (US) on single-stage mesophilic anaerobic digestion (AD) and temperature-phased AD (TPAD) treating wastewater sludge was assessed. The goal was to achieve a higher net energy along with improved digestate for agricultural applications. At sludge retention times (SRT) of 20 and 14 days, TPAD achieved significantly (39-45%) higher methane production, pathogen destruction (4-log) and digester volume reductions compared to single-stage AD (controls). The higher methane yields resulted in higher net energies for TPAD (4.7-5.1 kJ/g volatile solids or VS) compared to controls (3.3-3.7 kJ/g VS). Although improvements in organic removals and methane yields were observed after MW and US. the energy input for pretreatments were not compensated by the increased methane production, and therefore were concluded to be infeasible for industrial applications for single-stage and TPAD. All TPADs provided the highest pathogenic removal, and met the Class A biosolids fecal coliform requirements, while MW pretreatment achieved the highest fecal coliform removal for single-stage AD with digestates classified as Class B. Digesters incorporating thermal pretreatment (MW and MW + TPAD) yielded the highest amount of extra heat (4.2-5.8 kJ/g VS) that could be utilized within/outside of the facility. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: Anaerobic digestion; TPAD; Microwave; Sonication; Electrical energy; Pretreatment; ACTIVATED-SLUDGE; SEWAGE-SLUDGE; THERMAL PRETREATMENTS; SALMONELLA SPP.; FECAL-COLIFORMS; SOLUBILIZATION; IRRADIATION; PERFORMANCE; DISINTEGRATION; MECHANISMS